Effects of lycopene on spermatozoa morphology in balb/c mice exposed to 2-methoxyethanol (2-me) - Sitaresmi, Sandra Dewi; I'tishom, Reny; Mustika, Arifa (Folia Medica Indonesiana, 2017)
The compound of 2-methoxyethanol (2-ME) is one of toxic materials that potentially damage male reproductive organs. This compound can enter the body by various means of direct contact through the skin, respiratory and digestive tract. This compound can cause oxidative stress in spermatozoa which is the main cause of spermatozoa dysfunction. Lycopene, also known as red pigment, is an antioxidant class of carotene. Lycopene has antioxidant activity twice stronger than beta carotene and ten times stronger than vitamin E. Thus, the lycopene reaction as an antioxidant in the body is better than vitamin A, C, E, and other minerals. This study was conducted to determine the effects of lycopene on spermatozoa morphology in mice exposed to 2-ME. The study was conducted on 30 mice, divided into 5 groups. The K-group was the control group without 2-methoxyethanol and lycopene, the K + group was the group with 200 mg/kg BW 2-methoxyethanol on days 1-5, and the P1, P2 and P3 groups were the ones with 200 mg/kg BW 2-methoxyethanol on days 1-5 and lycopene doses of 5, 10 and 20 mg/kg BW on days 6-35. 2-ME was given intraperito-neally and lycopene was given per sonde. On day 36, the mice were sacrificed and the epididymis and vas deferens were removed for morphological examination of spermatozoa. The observations were performed using a microscope with 1000x magnification. The results showed that there was significant difference. In the morphology of spermatozoa, the administration of lycopene increases normal morphological percentage of spermatozoa in mice exposed to 2-ME.